Kinetics for Drug Discovery: an industry-driven effort to target drug residence time. Issue 6 (June 2017) - Schuetz, Doris A.; de Witte, Wilhelmus Egbertus Arnout; Wong, Yin Cheong; Knasmueller, Bernhard; Richter, Lars; Kokh, Daria B.; Sadiq, S. Kashif; Bosma, Reggie; Nederpelt, Indira; Heitman, Laura H.; Segala, Elena; Amaral, Marta; et al.
Highlights: A public–private partnership targets drug-binding kinetics in a multilevel approach. New experimental approaches for measuring drug residence time are presented. Standardized data formats will guarantee sustainability of the data generated. Progress in QSKR methods as well as mechanistic simulation approaches are discussed. In vitro to in vivo transition is key for adoption of kinetics for decision support. Abstract : A considerable number of approved drugs show non-equilibrium binding characteristics, emphasizing the potential role of drug residence times for in vivo efficacy. Therefore, a detailed understanding of the kinetics of association and dissociation of a target–ligand complex might provide crucial insight into the molecular mechanism-of-action of a compound. This deeper understanding will help to improve decision making in drug discovery, thus leading to a better selection of interesting compounds to be profiled further. In this review, we highlight the contributions of the Kinetics for Drug Discovery (K4DD) Consortium, which targets major open questions related to binding kinetics in an industry-driven public–private partnership. Teaser: Drug residence time is becoming increasingly important for decision support in the drug discovery process. Linking industry, SMEs and academia, the K4DD consortium is addressing drug-binding kinetics following a multidisciplinary approach.